Anal Cancer Screening in Men Who Have Sex With Men in the Multicenter AIDS Cohort Study. (15th April 2016) - D'Souza, Gypsyamber; Wentz, Alicia; Wiley, Dorothy; Shah, Nisha; Barrington, Francine; Darragh, Teresa M.; Joste, Nancy; Plankey, Michael; Reddy, Susheel; Breen, Elizabeth C.; Young, Stephen; Cranston, Ross D.
Abstract : Objective: To evaluate the prevalence of anal cytology (ACyt) abnormalities among HIV-infected and HIV-uninfected men who have sex with men (MSM). Design: Multicenter cohort study of 723 HIV-infected and 788 HIV-uninfected MSM with ACyt, with a second ACyt collected 2 years later. A referral for high-resolution anoscopy was suggested for abnormal ACyt. Methods: ACyt samples were collected using a polyester swab and liquid cytology media and read in a central laboratory. Results: Prevalence of any abnormal ACyt was 25% in HIV-uninfected MSM and increased to 38%, 41%, and 47% among HIV-infected MSM with current CD4 + T-cell counts ≥500, 350–499, and <350 cells/mm 3 ( P < 0.001), respectively. Anal HPV16 DNA was also more common in HIV-infected than HIV-uninfected MSM (25% versus 16%, P < 0.001). Abnormal baseline ACyt together with prevalent HPV16 DNA detection was present in only 7% of HIV-uninfected MSM compared to 18% of HIV-infected MSM with current CD4 < 350, P < 0.001. Among HIV-infected men, 56% of the men with atypical squamous cells of undetermined significance or low-grade squamous intraepithelial lesions ASCs-US/LSILs and 81% of men with atypical squamous cells cannot exclude high-grade (ASC-H/)/high-grade squamous intraepithelial lesions (HSIL) had lower grade ACyt findings 18–30 months later ("regressed"). However, 19% of untreated HIV-infected men with ASC-H/HSIL cytology maintained that same grade of cytology in their second test approximately 2 years later, and 15% with ASC-US/LSIL "progressed" to ASC-H/HSIL. Abnormal ACyt had high sensitivity (96%) but low specificity (17%) for biopsy-proven HSIL. Conclusions: Prevalence of abnormal ACyt remains elevated in HIV-infected men during the current antiretroviral therapy era. Abstract : Supplemental Digital Content is Available in the Text.